Colloidal stabilization of graphene sheets by ionizable amphiphilic block copolymers in various media. Issue 109 (20th October 2015) - Popescu, Maria-Teodora; Tasis, Dimitrios; Papadimitriou, Konstantinia D.; Gkermpoura, Sandra; Galiotis, Costas; Tsitsilianis, Constantinos
Abstract : Graphene nanosheet suspensions can be produced in organic solvents, water or ionic liquids by using the same ionogenic block copolymers. Abstract : In this work, linear polystyrene–poly(2-vinylpyridine) (PS- b -P2VP) and heteroarm star PS22 P2VP22 ionizable block copolymers were used as dispersing agents for the liquid-phase exfoliation of pristine graphene. Various strategies such as direct exfoliation, film hydration and phase transfer have been employed and compared. The best strategy involved a two-step process, namely, pre-exfoliation of graphite in polymer/CHCl3 solutions followed by phase transfer to acidified water. High concentrations of stable aqueous suspensions of graphene flakes, highly enriched in monolayer structures, were then obtained by using the star-shaped copolymers as stabilizers. The as-prepared graphene/copolymer hybrids were used as a filler material in order to prepare functional polymer composites for mechanical reinforcement. Such copolymer-modified graphene sheets have proven to be efficient reinforcing agents of PVA, as a significant increase of storage modulus (145% higher than that of neat PVA) was achieved even at a low graphene weight fraction of 0.1 wt%.